UNIVERSAL DESIGN FOR LEARNING (UDL) APPLICATION IN THE DESIGN OF LEARNING ENVIRONMENTS TO ENSURE EQUITY IN INCLUSIVE PRIMARY EDUCATION - Thi Bich Ngoc, Tran; Ha My, Nguyen; Minh Phuong, Nguyen (HNUE Journal of Science: Journal of Educational Science, 2024)
Universal Design for Learning (UDL) is implemented in inclusive education to ensure equal rights to learning, quality education, appropriate to the needs, characteristics, and abilities of learners; respect for diversity, differences of learners, and non-discrimination. However, there are still barriers to the inclusive learning process, including barriers in the learning environment that cause students with disabilities to encounter different difficulties. This article applies universal design for learning (UDL) in designing learning environments to ensure equity in inclusive education at the primary level, to point out barriers in the learning environment including the physical environment and the psychological environment of inclusive students at the primary level and suggestions for applying UDL in designing physical environments for learning to ensure equity in implementing inclusive education at primary level.